Internalisasi Nilai-Nilai Hadist dalam Kegiatan Pembelajaran Anak Usia Dini di TK Cerdas Sukorejo-Kendal : Penelitian - Kurniyah, Kurniyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Islamic value-based character education for early childhood plays a strategic role in shaping morals. However, internalization of hadith in early childhood education (PAUD) is still predominantly memorization-based and does not address affective and behavioral aspects. This study aims to describe the strategy for internalizing hadith values ​​in Smart Kindergarten Sukorejo-Kendal and explore children's responses and teachers' challenges. The method used is qualitative phenomenological with observation, interviews, and documentation, as well as analysis of the Miles and Huberman model. Validity is maintained through triangulation and member checking. The results show that the strategy for internalizing hadith through role models, habituation, storytelling, and Islamic songs and games effectively instills the values ​​of honesty, compassion, responsibility, and justice. Children show enthusiasm, remember the contents of the hadith, and imitate the teacher's behavior. Challenges include differences in family backgrounds, minimal home support, and limited media, which are overcome through parental communication and innovative teaching media. Conclusion: The holistic, contextual, and child-centered internalization of hadith values ​​effectively shapes Islamic character and is recommended for implementation in other PAUDs with the support of teacher training and family involvement.